ANALISIS ASIMETRI PEMBANGUNAN DAERAH DAN DINAMIKA KEMISKINAN ANTARPROVINSI DI INDONESIA: PENDEKATAN REGRESI DATA PANEL (2021–2025): ANALISIS ASIMETRI PEMBANGUNAN DAERAH DAN DINAMIKA KEMISKINAN ANTARPROVINSI DI INDONESIA: PENDEKATAN REGRESI DATA PANEL (2021–2025) - Nurviani Nurviani; Siti Hajar; Purwanto Purwanto; Darliah Darliah; Sayyidah Junaidah Al-Bahri; Lia Mulyani; Nurul Yusuf; Widiana Latifah; Dwi Rahayu Nurmiati (CV. Bunda Ratu, 2026)
This study examines the effects of the open unemployment rate (TPT), the human development index (HDI), and regional GDP per capita on the poverty rate across Indonesian provinces during 2021–2025. Using a quantitative explanatory design with a balanced panel dataset covering 38 provinces (190 observations) sourced from Statistics Indonesia (BPS), parameters were estimated using panel data regression with a Fixed Effect Model, selected after Chow and Hausman tests and classical assumption checks. The results show that the open unemployment rate has a positive and significant effect on poverty, while the human development index and GDP per capita have negative and significant effects. Together, the three variables explain 86.5 percent of the variation in poverty across provinces. The human development index emerges as the most elastic determinant, indicating that investment in human capital functions as the primary structural shield against poverty, more so than capital-intensive economic growth. These findings support a policy shift from aggregate, growth-oriented strategies toward inclusive, human-capital-based approaches, along with the revitalization of local labor markets in Indonesia's underdeveloped, frontier, and outermost regions.